2013
DOI: 10.1667/rr3153.1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dose Estimates for a Cohort of Belarusian Children Exposed to Radiation from the Chernobyl Accident

Abstract: The U.S. National Cancer Institute, in collaboration with the Belarusian Ministry of Health, is conducting a study of thyroid cancer and other thyroid diseases in a cohort of about 12,000 persons who were exposed to fallout from the Chernobyl accident in April 1986. The study subjects were 18 years old or younger at the time of exposure and resided in Belarus in the most contaminated areas of the Gomel and Mogilev Oblasts, as well as in the city of Minsk. All cohort members had at least one direct thyroid meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 26 publications
0
62
1
Order By: Relevance
“…We compared the arithmetic means of stochastic thyroid doses calculated in this study with the deterministic doses estimated previously (13) for the same cohort (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We compared the arithmetic means of stochastic thyroid doses calculated in this study with the deterministic doses estimated previously (13) for the same cohort (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…For some study subjects, the scaling factor was found to be very high (i.e., greater than 100) or very low (i.e., less than 0.01), and biases in the parameter values of the ecological model are not sufficient to explain these extreme values. Case examples of such study subjects were presented and analyzed in previous work (13). The results indicate that biases in parameter values cannot fully explain the discrepancies between the instrumental doses and in the ecological doses when the scaling factors are either very high or very low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations